PENGEMBANGAN GAME ARCADE 2D “FRUIT DASH” MENGGUNAKAN JAVASCRIPT PADA GAME ENGINE CONSTRUCT 3 - Putri, Endin Rahmanda; Atmaja, Pratama Wirya (Universitas Methodist Indonesia, 2024)
This research aims to develop a digital arcade game designed to train players' motor skills. The developed game, Fruit Dash, focuses on quick visual and motor responses. The game is built using the Construct 3 platform with JavaScript programming language. Fruit Dash features simple yet challenging gameplay, where players must throw bombs to destroy fruits falling from the air, with the primary goal of achieving the highest score. The development method used is the Game Development Life Cycle (GDLC), which includes the concept, production, and beta testing stages. Beta testing is conducted using a Likert scale to assess user experience, with results indicating high satisfaction in the aspects of visual design, controls, and game innovation. Overall, Fruit Dash can serve as a means to train motor skills through responsive gameplay